Optimal Location of FACTS Device on Enhancing System Security - Prakash Gajanan Burade; Jagdish Helonde (Institute of Advanced Engineering and Science, 2012)
In this paper a Unified Power Flow Controller (UPFC) is a FACTS device that can be control the power flow in transmission line by injecting active and reactive in voltage components in series with the lines.The proposed methodologies are based on the use of line loading security Performance Index (sensitivity factors have been suggested in this paper for optimal placement of UPFC.This methods are computationally efficient PI sensitivity factors have been obtained with respect to change in two of the UPFC parameters viz., magnitude and phase angle of the injected voltage in the lines. The proposed methodologies are tested validated for locating UPFC in IEEE 30-bus system.ACO based Optimal Power Flow (OPF) formulation has been suggested to determine the optimal PI values, after placement of UPFC based on the proposed sensitivity factors. Both AC and DC power flow approximations have been used to define the sensitivity factors and their results have been compared on IEEE 30-bus system.DOI:http://dx.doi.org/10.11591/ijece.v2i3.250